Job Satisfaction, Performance Level, and Supervisory Practices of Management in Adventist Medical Center Manila Basis For Program Formulation - Laura Aprilia Missah (Journal of Comprehensive Science, 2026)
This study is determined the relationships of job satisfaction, performance level, and supervisory practices of Management in Adventist Medical Center Manila to come up with the policy that was proposed which may be used to improve the job, performance level and supervisory practices of the employees. This study utilized descriptive research design, which, according to Fain (2013) “describe(s) and explain(s) the nature and magnitude of existing relationships without necessarily clarifying the underlying causal factors in the relationship.” This study is both descriptive and correlational. The subjects of this research study were the one hundred fifty (150) employees who were currently employed as regular and fifty-eight (58) managers in Adventist Medical Center Manila, consisting resident doctors and managers of different divisions/department. The total population of managers is fifty-eight (58).  All the 58 managers agreed to became respondents. The following findings were obtained: All of the employees’ job satisfaction indicators have the interpretation Satisfied. The overall weighted mean is 3.923 and and interpreted as Satisfied with the standard deviation equivalent to 0.1994; the employees’ job performance overall weighted mean is 3.692 and interpreted as Moderately Agree. This implies that the employees believed that they perform well based from the assigned task with less supervision and close monitoring; he overall weighted mean is 4.862 and interpreted as Strongly Agree with a standard deviation of 0.064. This implies that the middle managers believed that they consistently follow certain supervisory practices to ensure the success of their organization; It was found out that there is no significant relationship between the level of job performance and level of job satisfaction. Thus, the null hypothesis which states that there is no significant relationship between the level of Job Satisfaction and Job Performance of the respondents is accepted; The middle managers’ supervisory practices affects the employees’ job satisfaction; hence, the null hypothesis - there is no significant relationship between job satisfaction and supervisory practices is rejected. This is supported by the findings of the study of Hamzah, et al. (2013) which revealed that supervision practices have a positive and strong relationship with job satisfaction. In other words, if the level of supervision practices decreases, so will employees satisfaction; and the job performance and supervisory practices are significantly related, therefore the null hypothesis - there is no significant relationship between job performance and supervisory practices is rejected. The middle managers’ supervisory practices play an important role and have an effect on the employees’ job performance.